A history of Christian thought ; v. 1 - Gonzalez, Justo L. (Nashville, TN Abingdon, 1970)
Contents : v. 1 : From the beginnings to the Council of Chalcedon. Includes bibliographical references and index.
Keywords: Theology, doctrinal -- history